A trve discovrse of the present estate of Virginia, and the successe of the affaires there till the 18 of Iune, 1614 : together, with a relation of the seuerall English townes and forts, the assured hopes of the countrie and the peace concluded with the Indians. The christening of Powhatans daughter and her mariage with an English-man - Hamor, Ralph, -1626 (LLMC-digital (Series), 1615)
A True discourse of the present estate of Virginia, written by Raphe Hamor the younger, and printed in London in 1615. This volume, which was written by the past secretary of the Virginia Company after his return to London, detailed the marriage of Pocahontas and John Rolfe, as well as Rolfe's cultivation of tobacco, the martial administration of Sir Thomas Dale, and the establishment of the city of Henrico. Also included are copies of letters written by Thomas Dale, John Rolfe, and Alex. Whitaker.